Cell Death - Autophagy, Apoptosis and Necrosis 2015
DOI: 10.5772/61654
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Molecular Advances in Breast Cancer Management

Abstract: Breast cancer is the most common cancer type amongst women, accounting for most female cancer deaths second to cervical cancer worldwide. It is, therefore, highly crucial to understand the molecular biology and explore other pathways involved in carcinogenesis in order to select appropriate treatment not only for breast cancer but for other cancers as well. Cancer progression is favoured by DNA damage and in most cases a consequent disruption of the apoptotic pathway, thus leading to uncontrolled cell prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
(100 reference statements)
2
2
0
Order By: Relevance
“…Necrosis was considered to be a physical process of cell death that was not regulated. However, emerging evidence suggests that it is as another form of apoptosis and an independent genetically encoded cell death pathway [25,26]. Overall, treated cells with the three types of PBDs exhibited similar ultrastructural changes exhibiting distinct features such as the increased number of vacuoles portraying as a defense mechanism for cell survival and this is consistent with other studies in other types of cancers [27][28][29].…”
Section: Effect Of Pbds On the Intracellular Organelles Of Breast Cansupporting
confidence: 87%
See 1 more Smart Citation
“…Necrosis was considered to be a physical process of cell death that was not regulated. However, emerging evidence suggests that it is as another form of apoptosis and an independent genetically encoded cell death pathway [25,26]. Overall, treated cells with the three types of PBDs exhibited similar ultrastructural changes exhibiting distinct features such as the increased number of vacuoles portraying as a defense mechanism for cell survival and this is consistent with other studies in other types of cancers [27][28][29].…”
Section: Effect Of Pbds On the Intracellular Organelles Of Breast Cansupporting
confidence: 87%
“…We then used TEM to gain further insight into the ultrastructural alterations induced by PBDs and to study how the drug cytotoxicity differentially caused these alterations. Other distinct morphological characteristics of apoptosis consistent with the literature were evident such as shrinkage of the cytoplasm, microvilli retraction, fragmentation and condensation of the nucleus and swelling of both the mitochondria and endoplasmic reticulum [24,25]. Splitting of apoptotic cells characterizes the final stage of apoptosis [24].…”
Section: Effect Of Pbds On the Intracellular Organelles Of Breast Cansupporting
confidence: 69%
“…41 Apoptosis breaks down in cancer is a result of three mechanisms, including loss of function of death receptors, a reduction in the caspase activity, and the imbalance between apoptotic and antiapoptotic factors. 42 Another essential factor in breast cancer pathogenesis is epigenetic influences, which involve improper changes in DNA and histone that inhibit tumor suppressor gene expression. Eventually, these changes, like DNA methylation, leads to tumor progression.…”
Section: Pathogenesis Of Breast Cancermentioning
confidence: 99%
“…The key regulator genes of apoptosis have been targeted through several fungal endophyte-derived bioactive compounds to combat the deadliest disease like cancer. [17][18][19] Besides, various studies have reported the anticancer potential of biologically engineered silver nanoparticles mediated by fungal endophytes. 20,21 Whereas, due to its small size, the nanoparticle of silver can easily enter the bloodstream and may induce toxicity to many organs, including the brain, spleen, heart, liver, and kidney by altering various physiological and biochemical parameters.…”
Section: Introductionmentioning
confidence: 99%